PENGARUH EKSTRAK METANOL DAUN KESUM (Polygonum minus Huds.) TERHADAP PENINGKATAN KADAR KREATININ DAN UREUM SERUM TIKUS PUTIH GALUR WISTAR TERINDUKSI SISPLATIN - ., Michael (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2013)
Cisplatin is a chemotherapy drug that had nephrotoxicity side effect which marked with the increase of urea and creatinine. Kesum (Polygonum minus Huds.) is one ofthe potential herbs that can be used to decrease urea and creatinine concentration. Thepurposes of this research is to find out the secondary metabolite contents of kesumleaves methanol extract and the activity of urea and creatinine concentrationreduction which rats were treated to have nephrotoxic with induction of cispatin.Kesum leaves extraction was done by maseration method using methanol solvent.Phytochemical screening test was perfomed with a tube to detect the compound inkesum leaves extract. The rats were divided into 5 groups which are non-treatedgroup (CMC1%), cisplatin control group, dose 1 group (8,664 mg/200 grBW), dose 2group (17,328 mg/200 grBW), and dose 3 group (34,656 mg/200 grBW). Theconcentration of urea and creatinine were checked at day 10 after the induction usespectrophotometer UV-Vis. Data were analyzed with Oney Way ANOVA and PostHoc Test Multiple Comparisons-Tukey HSD test. Phytocemistry screening showsthat kesum leaves methanol extract compound alkaloid, polyphenol, tannin,flavonoid, triterpenoid and saponin. The results show that dose 1, dose 2, and dose 3can decrease urea and creatinine concentration which indicate that it has potency toreduce the side effect of chemotherapy agent cisplatin.